COURSE OF HERPES VIRUS IN HIV INFECTION - Khazhimatova Guzal Marufzhanovna (Scholar Express Journals, 2023)
The main feature of herpes viruses is their lifelong persistence in the body, even if a person is infected once. The course of a chronic infectious process depends on the state of the immune system of the virus carrier [6]. Viral reactivation aggravates secondary immunodeficiency. Manifestations of herpetic infection are many-sided - from rashes on the lips and aphthous stomatitis to generalized forms with widespread damage to the skin and mucous membranes involving various organs and systems in the pathological process.
Keywords: Herpes viruses; systems; pathological process.; generalized